A 'double edged sword': discretion and compulsion in policing domestic violence*. (4th July 2017) - Diemer, Kristin; Ross, Stuart; Humphreys, Cathy; Healey, Lucy
Abstract: Policing domestic violence is a complex area in which there are divergent views about the extent to which front line police action should be mandated by legislation and guidance. This study set in Victoria, Australia raised questions about the balance between discretion and compulsion in policing domestic violence through researching the implementation of the Code of Practice used to respond to domestic violence incidents. The project team interrogated aggregate data from the police database on family violence and also interviewed 125 police members (60 sergeants and 65 constables) to explore the attitudes to the Code of Practice and policing domestic violence. The findings reveal that discretion within a range of options is circumscribed. Variable understandings of the nature of domestic violence and the role of risk assessment and management suggest that constrained and guided discretion may be required to achieve optimum effectiveness in policing responses to domestic violence.